A formulação da descontinuidade na crítica de arquitectura contemporânea ou a transitoriedade da tradição - Rui Jorge Garcia Ramos (2011)
The theme of discontinuity is frequently used as an interpretation tool of the recent Portuguese architecture. This theme and the topics related to it are adopted in a vast number of articles (between 1998 and 2005) that share common understandings on contemporary architecture. This phenomenon observed in architecture's critique is our object of reflexion. Above all, we intend to oppose ideas and presuppositions from this critique that, when not attending the historical process and the 20th century Portuguese architecture status proposes, in first place, an imprecise and hegemonic reading of the contemporary creation. In our opinion, this stance "forces" an interpretation that does not correspond to a more extensive and deep knowledge of which the 20th century Portuguese architecture allows and demands.The critical positioning that we now discuss aims to identify a new sense in recent Portuguese architecture. In this way, architecture is seen as fragmented, discontinuous, fluid... a mapping of causality, with which it is intended to reconstruct, both the binominal form/construction of architecture, and its public sense. It intends to place the subject before a new mutant and dynamic reality, increasingly marked by an European identity and for which the Portuguese disciplinary tradition has come to find difficulties in fitting in.This reading questions the inclusion of a notion of time in the project. In other words, the acceptance of the past and its inclusion in a line of knowledge - the tradition - as the basis of the project. This acceptance is one of a continuous movement throughout past, present and future, where the project occupies a space between what can be and what may be. Informed by the past and present, the project, without being the preparation of a future, is the conjunction of several actions that determine possibilities for the future. Without the recording of this dialectic process, the project's culture suffers from a rapid degradation, tending to abandon an intervention oriented to the qualification of our existence and of the social sphere.In the absence of the observation of this commitment and balance within the project that runs in this time arch, the present assumes an omnipresent role in the project which, when ignoring history, allows the reconsideration that everything is permanently new. The exclusion of historical knowledge in the project's formulation, as a qualifying action of existence, not only will lead to "the destruction of the past" but also to the elevation of the present, necessarily tutored by masters and works in the leading of the new.This essay explores the existent divergence, although enriching, between the critique/theoretical discourse about the recent production and the architectonic projects that give continuity, in their generality, to the phylogeny lines of Portuguese architecture, namely the 20th century.